FEASIBILITY STUDY OFPOLYMER-BASEDMICROCHANNEL HEAT SINKASTHERMAL SOLUTIONUSINGCOMPUTATIONALFLUID DYNAMICS - YUE , ONG SEONG (2020)
This research aims to numerically investigate the feasibility of polymer-based microchannel heat sinks(MCHSs)as thermal solutions using computational fluid dynamics (CFD). ANSYS 19.1 was used. Lightweight aspect has been given huge emphasis in recent years. Metal-based materials are commonly used to fabricate MCHSs due to their high thermal conductivity. Consequently, MCHSs are heavy due to the high density of these materials albeit the small footprint of MCHSs. Polymer-based materials are interesting alternatives